Effect of a rotating cylinder in forced convection of ferrofluid over a backward facing step - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2014)
In this study, numerical analysis of the heat transfer enhancement and fluid flow characteristics of a rotating cylinder under the influence of magnetic dipole in the backward facing step geometry is conducted. The governing equations are solved with a finite element based commercial solver. The effects of Reynolds number (10 <= Re <= 200), cylinder rotation angle (-75 <= Omega <= 75) and strength of the magnetic dipole (0 <= gamma <= 16) on the heat transfer characteristics are studied for backward facing step flow. It is observed that the length and size of the recirculation zones can be controlled with magnetic dipole strength and cylinder rotation angles. As the Reynolds number increases, local Nusselt number increases and number of peaks in the presence of the magnetic field decreases. The effect of cylinder rotation on the local Nusselt number distribution is more pronounced at low Reynolds number. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Magnetic dipole; Rotating cylinder; Backward facing step; CFD